Proceedings of the 2016 ACM Conference on International Computing Education Research 2016
DOI: 10.1145/2960310.2960319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Frame-based Programming Editor

Abstract: Frame-based editing is a novel way to edit programs, which claims to combine the benefits of textual and block-based programming. It combines structured 'frames' of preformatted code, designed to reduce the burden of syntax, with 'slots' that allow for efficient textual entry of expressions. We present an empirical evaluation of Stride, a frame-based language used in the Greenfoot IDE. We compare two groups of middle school students who worked on a short programming activity in Greenfoot, one using the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…However, we found no effect on task performance in terms of correctness or speed. This matches the result of an observational study that looked at Java vs Stride in a school setting with teenagers and found no difference in performance on a series of code writing task across multiple lessons [11], although a prior study had found some differences in task completion rate [32]. Overall, it seems that high-level behavioral measures are often invariant to the way in which the code is presented, presumably because any high-level effect of presentation differences is small.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we found no effect on task performance in terms of correctness or speed. This matches the result of an observational study that looked at Java vs Stride in a school setting with teenagers and found no difference in performance on a series of code writing task across multiple lessons [11], although a prior study had found some differences in task completion rate [32]. Overall, it seems that high-level behavioral measures are often invariant to the way in which the code is presented, presumably because any high-level effect of presentation differences is small.…”
Section: Discussionsupporting
confidence: 80%
“…Stride has been compared to Java in two existing studies of code writing. Price et al [32] examined the differences in a US school setting and found some differences in the rate of task completion, with Stride being faster. Brown et al [11] conducted a study involving multiple different UK schools and found no interface effect in a set of code writing tasks, either in task completion time or understanding of object orientation.…”
Section: Role Of Scope Highlighting In Code Understandingmentioning
confidence: 99%
“…Early work on graphical (but not block-based) programming [24] found little evidence of successful transfer of basic programming tasks in novices when moving to text-based programming languages despite prior programming success with graphical tools. Similar outcomes have been documented using contemporary block-based environments, with case studies documenting challenges associated with the transition [9,13,21]. On the contrary, there are studies showing that programming skill and knowledge gains made in block-based tools do prepare learners for later text-based programming.…”
Section: Transitioning From Blocks To Textmentioning
confidence: 56%
“…Some changes are at the user interface level while other accommodations are deeper in terms of new or redesigned features. An example of this is the Stride frame-based editor used in tools such as Greenfoot [12]. This editor enables users to work with operations and constructs at an abstract level.…”
Section: Next Stepsmentioning
confidence: 99%